Optimization of South Sumatra Province Rubber Supply Chain with Price Monitoring Application: Optimization of South Sumatra Province Rubber Supply Chain with Price Monitoring Application - Nolan Efranda; Irvai, Muhammad (ADPEBI, 2022)
Problems that occur in the rubber supply chain in the province of South Sumatra cause the supply process or distribution of the results of smallholder rubber processing to be hampered. The scope of this research covers areas in the province of South Sumatra. The purpose of this study is to optimize the rubber supply chain model in the province of South Sumatra from several existing supply chain channels using website-based applications and Quantitative Management (QM) applications for data analysis. The analytical method used is the Linear Programming (LP) method. Transport capacity and labor hours are used as constraint functions while the objective function is optimization. There are three rubber supply chain channels in the province of South Sumatra. From the results of testing the Quantitative Management (QM) application on the first channel with a sample of farmers A1, village collectors B1 and district collectors Z1 in the first supply chain in March 2022, the product solution type X2 is 585.71 and profit X2 = 9745, then the profit is obtained of Rp. 5,707,786. From the results of testing the Quantitative Management (QM) application on the second channel with a sample of farmers A2 and large collectors B2 on the second channel in March 2022, the type A product solution is 276.32 and the profit is X1 = 12125, then the profit is Rp. 3.350.5329. From the results of testing the Quantitative Management (QM) application on the third channel with samples of farmers A3 and B3 on the third channel in March 2022, it was found that the type B product solution was 525 and the profit X2 = 12750, the profit was Rp. 6.693.750. So based on the results of the analysis on the QM application, the optimal profit from the supply chain in South Sumatra is in the third channel.